Improving the English speaking ability for pre-intermediate adult learners by using pairwork and groupwork in class at Hanoi branch of Ho Chi Minh national political academy/Nguyễn Văn Lương; Lê Thị Hồng supervisor. - Nguyễn, Văn Lương.
Includes bibliography and appendices